Targeting p53 and histone methyltransferases restores exhausted CD8+ T cells in HCV infection - Valeria Barili; Paola Fisicaro; Barbara Montanini; Greta Acerbi; Anita Filippi; Giovanna Forleo; Chiara Romualdi; Manuela Ferracin; Francesca Guerrieri; Giuseppe Pedrazzi; Carolina Boni; Marzia Rossi; et al. (Nature Communications, 2020)
Here, the authors report that exhausted HCV-specific CD8+ T cells are marked by upregulation of p53 signaling already detectable in an early phase of chronic HCV infection and by a later development of a repressive chromatin state, and show that chemical targeting of these pathways improves CD8+ T cell metabolism and antiviral function.